A Novel Approach to Postoperative Ear Pain—Greater Auricular Nerve Block Catheter: A Case Report. Issue 1 (1st January 2020) - Ellison, Matthew B.; Howell, Stephen; Heiraty, Payam; Wilson, Colin; Shepherd, Jason; Ellison, Pavithra R.
Abstract : A 70-year-old man presented for repair of an ear avulsion injury sustained from an all-terrain vehicle accident. A continuous technique using a catheter for a greater auricular nerve (GAN) block was performed in the preoperative area followed by general anesthesia in the operating room. No opioids were administered during the surgical procedure or in the immediate postoperative period. The GAN catheter was kept in place for 3 days with near-complete pain relief per the patient. To our knowledge, there are no case reports that describe a continuous GAN technique for surgery and postoperative pain.